Analysis of growth resistance mechanisms and causes in tea plants (Camellia sinensis) in high-pH regions of Northern China - Li, Chun-Lei; Xu, Jing; Xu, Hong-Mei; Liu, Jie; Zhang, Long-Xiang; Wang, Zi-Kai (Frontiers in Nutrition, 2023)
In tea plantations with high pH (pH>6.5) of northern China, tea trees are prone to yellowing disease, albinism and quality component declining, which affect the scale and rate of development of tea plantations in northern China. In order to investigate the causes of these occurrence, Pingyang Tezao and Ruixue, were planted in Shouguang (high pH area) and Rizhao (normal pH area), respectively, and the differences in growth morphology, pigment content, cell structure, quality components, element content of the two varieties in the two areas were analyzed. The results showed that tea leaves planted in Shouguang indicated different degrees of yellowing disease and albinism; pigment contents in both varieties were significantly lower than those in the Rizhao planting; cell structure was severely damaged, the main quality components were decreased; the content of Nitrogen (N), Phosphorus(P), Potassium(K), Zinc(Zn), Copper(Cu) and Manganese(Mn) in the leaves of two tea tree varieties planted in Shouguang were significantly lower than those in the leaves of varieties planted in Rizhao, while these elements in the soil of Shouguang were significantly higher than those in the soil of Rizhao, therefore, the soil in high pH area hindered the uptake of N, Zn, Cu and Mn by tea trees, causing the chloroplasts to suffer and the chlorophyll synthesis to be hindered, which is the main reason for the yellowing disease and albinism phenomenon of tea tree leaves, in addition, the excessive calcium (Ca) in Shouguang soil is also an important reason. The high pH soil hinders the uptake of P and K by tea trees, causing the decline of tea polyphenols, amino acids and other major quality components.